2004
DOI: 10.1099/ijs.0.02953-0
|View full text |Cite
|
Sign up to set email alerts
|

Kribbella solani sp. nov. and Kribbella jejuensis sp. nov., isolated from potato tuber and soil in Jeju, Korea

Abstract: Two actinomycete strains, DSA1 T and HD9 T , were isolated from a potato tuber and soil from a potato-cultivating field in Jeju, Korea, respectively. A comprehensive 16S rDNA analysis revealed that the isolates belong to the genus Kribbella and share 97?7-98?6 % sequence similarity to Kribbella species. The strains also contained typical chemotaxonomic markers of the genus Kribbella: LL-diaminopimelic acid, alanine, glycine and glutamic acid in the cell wall peptidoglycan; mannose, glucose, galactose and ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The gene sequence showed high similarity with those of the genus Kribbella, such as Kribbella aluminosa (JCM 14599 T , 1419/1432 bp, T: Type strain, 99.1%) 11 and K. solani (JCM 12205 T , 1433/1453 bp, 98.6%). 12 These phenotypic and genotypic data suggested that strain MI481-42F6 belongs to the genus Kribbella. Therefore, the strain was tentatively designated as Kribbella sp.…”
Section: Resultsmentioning
confidence: 97%
“…The gene sequence showed high similarity with those of the genus Kribbella, such as Kribbella aluminosa (JCM 14599 T , 1419/1432 bp, T: Type strain, 99.1%) 11 and K. solani (JCM 12205 T , 1433/1453 bp, 98.6%). 12 These phenotypic and genotypic data suggested that strain MI481-42F6 belongs to the genus Kribbella. Therefore, the strain was tentatively designated as Kribbella sp.…”
Section: Resultsmentioning
confidence: 97%
“…Although the chemical potential of the genus has not been evaluated extensively to date, some species have shown a high potential for producing the following new bioactive agents: Kribbella koreensis, which produces neuropilin/growth factor complexes [ 19 ], Kribbella antibiotica, which shows antifungal activity [ 20 ], Kribbella jejuensis that inhibits the growth of Streptomyces scabiei [ 21 ], and Kribbella sp. UTMC 267 has been proven to possess anti-calcification properties [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The potential for hydrolytic activity, particularly beta-glucosidase activity, was also shown for bacteria belonging to the genera Microlunatus [60] and Kribbella. In particular, K. jejuensis was mentioned for its utilisation of xylan and cellobiose [61].…”
Section: Plos Onementioning
confidence: 99%